Fire retardancy behavior of PLA based nanocomposites - Herrero, Berta (2013)
To understand and improve the fire retardancy behavior of polylactic acid, we have incorporated two structurally different additives, sepiolite and organically modified montmorillonite. A novel approach (combination of electrospinning and extrusion/injection molding) is employed to address critical issues like char enhancement as well as the homogeneity/uniformity of the inorganic barrier during combustion of polymer nanocomposites. Fundamental knowledge is gained on the mechanisms of fire retardancy, particularly with samples of different thicknesses (thermally thin versus thermally intermediate/thick). Volumetric imaging of the residues provided a deeper understanding of the formation or the evolution of the inorganic barrier. Considerable insight on the dependency of biodegradation on the environment (primarily) and on the compromising effect of high aspect ratio nanoparticles is also obtained. This knowledge has a broader scientific impact and is critical to design the new generation of eco-benign flame retardant and biodegradable polymer nanocomposites.